Development of Learning Media by Applying Scratch Assisted Computational Thinking Oriented to Self-Regulated Learning and Students' Mathematical Problem-Solving Skills - Anis Widiyanti; Dhoriva Urwatul Wutsqa (Asosiasi Riset Ilmu Matematika dan Sains Indonesia, 2026)
This study developed and evaluated interactive Scratch-based learning media integrating computational thinking to support students’ self-regulated learning and mathematical problem-solving ability. The research used a Research and Development approach by adapting the ADDIE model: Analysis, Design, Development, Implementation, and Evaluation. Participants were 11 eleventh-grade students and one mathematics teacher at SMK PIRI 1 Yogyakarta. Data were collected through expert validation sheets, teacher and student response questionnaires, learning implementation observations, a mathematical problem-solving test, and a self-regulated learning questionnaire. Qualitative and quantitative analyses included multivariate and univariate normality tests, Hotelling’s T² test, and one-sample t-tests using RStudio. The results indicated that the developed media met validity and practicality criteria. Experts declared the media valid, while the teacher rated it very practical, students rated it practical, and implementation exceeded 80%. The media was effective in improving self-regulated learning, with a significance value of 0.006371, a mean score of 3.8, and 74.99% mastery. However, the proportion test did not confirm that mastery exceeded the predetermined criterion. Mathematical problem-solving ability also failed to meet the minimum effectiveness criterion, with a significance value of 0.1792, a mean score of 77.04, and 64% mastery. Therefore, the media requires refinement to strengthen students’ mathematical problem-solving outcomes consistently.